Automatic Question Generation from Queries - Lin, Chin-Yew (2008)
With increasing popularity of communitybased question answering services such as Yahoo! Answers, huge amounts of user generated questions are available. In this paper, we propose using these data along with search engine query logs to create a question generation shared task that aims to automatically generate questions given a query. At least two benefits could result from such a task. First, it can be used to rank possible candidate questions; therefore, it would enable search of question answer archives. Second, it could be used as a more informative and richer way of query expansion to guide or aid search.